Public Health in the Precision-Medicine Era - Bayer, Ronald; Galea, Sandro (The New England journal of medicine, 2015)
The burgeoning precision-medicine agenda focuses on detecting and curing disease at the individual level, but there are multiple contributors to the production of population health, and clinical intervention cannot remedy health inequities. That clinical medicine has contributed enormously to our ability to treat and cure sick people is beyond contention. But whether and to what extent medical care has transformed morbidity and mortality patterns at a population level and what contribution, if any, it has made to the well-being and life expectancy of the least-advantaged people have been matters of contention for more than a century. This debate has taken on renewed importance as the scientific leadership at the National Institutes of Health (NIH), National Academy of Medicine, and U.S. universities have taken up the challenge of personalized or precision medicine. It . . .